The impact of corporate social responsibility on the reputation of local companies (Case study with companies in Kosovo) - Lima, Demir; Sejdiu, Sherif; Kastrati, Taulant; Shala, Venet (Edelweiss Applied Science and Technology, 2025)
This study aims to examine the relationship between corporate social responsibilities in Kosovo and their reputation in the market and in society, focusing on the impact that CSR has on the company's image. This type of research is descriptive research, for which an online survey, a self-administered survey, was used to collect data for this purpose. The sample consisted of 52 consumers and various individuals in Kosovo. The results show that corporate social responsibility (CSR) is positively related to corporate reputation; as social responsibility increases, corporate reputation increases. A limitation of the study is the limited size of the research participants, with only 52 individuals participating. Only those individuals who had the opportunity to access the questionnaire via the link distributed online participated in the research. Therefore, not every individual in the population had an equal opportunity to be included in the sample. Additionally, the sample size for this research was limited due to the short time period. For future research, it is recommended that the questionnaire be applied to more consumers and differentiated individuals in order to determine in more detail whether corporate social responsibility is affecting corporate image and goodwill.